Implementation of the Moving Class System to Improve Students’ Learning Motivation at a Vocational High School - Fatma Rosanti; Nunung Nurjanah; Widiyanti Widiyanti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to analyze the effect of implementing the moving class system on students’ learning motivation at SMK Islam 2 Wlingi. This study was motivated by students’ low learning motivation, which was attributed to conventional instruction that was static and monotonous. This study used a descriptive qualitative approach involving 33 participants: 30 students, 2 teachers, and 1 vice principal. Purposive sampling was used to select participants who were directly involved in implementing the moving class system. Data were collected through non-participant observation, semi-structured interviews, and documentation, then analyzed using Miles and Huberman’s interactive model and thematic analysis to identify patterns of change in students’ learning motivation. The results showed that implementing the moving class system had a positive effect on students’ learning motivation. This improvement was indicated by increased enthusiasm, focus, discipline, and responsibility during learning activities. Variations in the learning environment through classroom transitions reduced boredom and increased students’ active engagement. In addition, this system encouraged students to become more independent in managing their time and preparing for their learning needs. Nevertheless, several challenges were identified, including physical fatigue and confusion during the initial stage of implementation. This study concluded that the moving class system was an effective instructional innovation for increasing students’ learning motivation